Characterizing desired futures of Canadian communities. (September 2016) - Cameron, Laura; Potvin, Catherine
Highlights: We conduct a meta-analysis of future visions created by communities across Canada. We compare desires according to social, economic, and environmental sustainability. The social pillar of sustainability is most widely represented in the desired futures. Community visions can provide a basis for a regenerative approach to sustainability. The Sustainable Canada Dialogues can connect public desires with expert scenarios. Abstract: In sustainability research and practice, one method widely used in exploration is visioning, in which desirable sustainable futures are articulated and explored in depth. Communities across Canada have used this method to develop collective desirable futures, in many cases to provide an end goal for local sustainable development. In this paper, we conduct a meta-analysis of desired futures created by communities across Canada with the aim of identifying regional commonalities according to the three pillars of sustainability, social, environmental, and economic. Although sustainability demands a balance between its social, economic and environmental components, Canadians futures apparently place the greatest importance on social aspects with 338 desires against 222 and 230 respectively for economic and environmental sustainability. Community (105); Infrastructure, development, and transportation (126); and Natural environment (157) are the categories most frequently recorded within each of the three components of sustainability. The metaanalysis also noted significant differences amongst regions. The study was conducted in the context of an initiative known as the Sustainable Canada Dialogues that mobilized 60+ scholars from across the country around a consensus on science based, viable solutions for greenhouse gas reduction. Our results suggest that climate policy that simultaneously reduces greenhouse gas emissions while enhancing some of the key aspects of social sustainability would be attractive to many Canadians.